Kampanye lewat Media Sosial Mengenai Pentingnya Daerah Resapan Air - Chandeni Dwi; Dimas Anggi; Fitriatul Khasanah; Tutut Chusniyah (Flourishing Journal, 2023)
The land conversion that is carried out will be very beneficial for the community, but unfortunately a lot of development is being carried out on catchment land that is not in accordance with existing regulations and does not pay attention to the capabilities of the land. If the development is not in accordance with the existing provisions regarding land conversion in catchment areas, then negative things such as annual flooding that occurs in the lower plains will have a negative impact on the community and also the government. Therefore, one of the efforts to raise public awareness about water catchment areas is to provide a basic understanding of water catchment areas, and also how to protect water catchment areas. Implementation of a social media campaign by uploading posts about water catchment areas is one of the intervention efforts that can be implemented by the community to protect the environment. Then the results of the social media campaign program are very effective because they can reach all levels of society who read them. So as to increase public understanding about water catchment areas and also move in preventing negative impacts from the conversion of water catchment areas. AbstrakAlih fungsi tanah yang di jalankan akan sangat dapat bermanfaat bagi masyarakat namun sayangnya banyak pembangunan yang di lakukan di tanah resapan yang tidak sesuai dengan ketentuan yang ada dan tidak memperhatikan kemampuan tanah. Jika pembangunan pada alih fungsi lahan pada daerah tanah resapan tidak sesuai dengan ketentuan yang ada maka hal negatif seperti banjir tahunan yang terjadi di dataran yang lebih rendah akan menjadi dampak yang buruk bagi masyarakat dan juga pemerintah. Maka dari itu salah satu upaya utuk menumbuhkan kesadaran masyarakat mengenai daerah resapan air adalah dengan memberikan pemahaman dasar tentang daerah resapan air dan juga cara menjaga daerah resapan air. Pelaksanaan kampanye media sosial dengan cara mengunggah postingan mengenai daerah resapan air menjadi salah satu upaya intervensi yang dapat di terapkan oleh masyarakat untuk menjaga lingkungan. Hasil dari program kampanye media sosial inu menjadi sangat efektif karena dapat menjangkau seluruh lapisan masyarakat yang membacanya. Sehingga menambah pemahaman masyarakat mengenai daerah resapan air dan juga bergerak dalam mencegah dampak negatif dari alih fungsi daerah resapan air.